Large Geographical Area Aerial Surveillance Systems Data Network Infrastructure Managed by Artificial Intelligence and Certified Over Blockchain: a Review - Batista, Nelson (2022)
This paper proposes an aerial data network infrastructure for large geographical area surveillance systems. The work presents a review of previous works from the authors, existing technologies in the market and other scientific work, with the goal of creating a data network supported by Autonomous Tethered Aerostat Airships used for sensor fixing, drones deployment base and meshed data network nodes installation. The proposed approach for data network infrastructure supports several independent and heterogeneous services from independent, private and public companies. The presented solution employs Edge Artificial Intelligence (AI) systems for autonomous infrastructure management. The Edge AI used in the presented solution enables the AI management solution to work without the need of a permanent connection to cloud services and is constantly feed by the locally generated sensor data. These systems interact with other network AI services to accomplish coordinated tasks. Blockchain technology services are deployed to ensure secure and auditable decisions and operations, validated by the different involved ledgers.